A formação literária de Fiodor Dostoievski e o conceito de Homem Pequeno - Pontes, Madjer Ranyery de Souza (2015)
This thesis aims to analyze the literary formation of the Russian novelist Fyodor Mikhailovich Dostoevsky (1821-1881), noting, in particular, key aspects of the first phase of his work (1846-1861), and to investigate the development of the concept of "small man" in his writing. That way, we will seek to articulate the artistic conceptions of the novelist with the other representatives of thought and Western European literature. We investigate the major social and artistic representations present in the first half of the European nineteenth century to delineate the main historical, aesthetic and philosophical convergence in the genesis of Russian thought nineteenth century and the cultural development of Dostoevsky, placing it in the Russian literary scene then. Present the historical arrangements for the establishment of the city of St. Petersburg as the Imperial capital, held by Peter I the Great (1672-1725) and the consequences of that foundation in the life of the "small man" Russian. Then articulates the formation of Dostoevsky with literary criticism and essays of his time, emphasizing its role as one of the most innovative representatives of thought and literature in Russia. To this end, we will use the debut novel of Dostoevsky's Poor People, 1846, to discuss and analyze the relationship between poverty and literature, emphasizing the humanistic values developed in the first work of the novelist.